Processos de subjetividades, interações e pertencimento na banda de música escolar : um estudo de caso na Banda Marcial Ranulpho Paes de Barros, em Cuiabá/MT - Costa, Francisval Candido da (2020)
This research aims to investigate the processes of resignification of culture and belonging in Marching Band Ranulpho Paes de Barros, located in the Santa Isabel neighborhood, in Cuiabá City (Mato Grosso, Brazil). It was considered necessary to understand the processes of resignification of band culture, and the subjectivities that occur in the process of interaction between cultural actors and the relationship of belonging. The specific objectives are: to carry out a bibliographic study involving culture, band and belonging; to investigate the reframings of a specific group in the studied band; and to verify the lessons learned from the relationship that this group of components establishes with music and with the others. The methodology used contemplates the case study in a qualitative approach, with the aforementioned band as the object of investigation. The methodological procedures involved bibliographic research, documentary research, participant observation - the researcher is the conductor of the investigated band - and interview with a selected group. The bibliographic research was based on studies about bands by the following authors: Alves da Silva (2018), Campos (2008), Soares (2018) and Lima (2000, 2005). And the concept of culture and belonging are based in Hall (2003), Williams (1992), Maffesoli (2014) and Castro (2011). It was verified, through the analyzed data that invitation, the circle of friends, previous experience, love for music, and learning to play a musical instrument are presented as motivations found by students in the process of participation in the band. And what corresponds to the questions regarding the experiences in the learning of the band's musicians are: the difficulties encountered in learning the instrument, the skills acquired during this learning process, the study/learning practices developed by them (and by the band's teachers) and the performances collaborative demonstrates the processes by which these students seek to practice this knowledge for the cultural construction and belonging of group.